2018
DOI: 10.1155/2018/6124927
|View full text |Cite
|
Sign up to set email alerts
|

Change of Circulating and Tissue-Based miR-20a in Human Cancers and Associated Prognostic Implication: A Systematic Review and Meta-Analysis

Abstract: Background Previous literatures have investigated the change of miR-20a expression level in the progression of multiple cancers and its influence on patients' survival outcome, but results of now-available evidence are inconsistent. Objective To elucidate the prognostic value of circulating and tissue-based miR-20a for patients with various cancers. Methods A systematic search and review of eligible publications were carried out in three electronic databases including the Cochrane Library, PubMed, and Embase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 52 publications
(126 reference statements)
1
8
1
Order By: Relevance
“…Porkka et al, (2007) identified 51 individual miRNAs which differentially expressed between benign and malignant tumors, among which, 37 showed down-regulation and 14 showed up-regulation in carcinoma samples. In other studies higher levels of miR-20a expression were shown in more dedifferentiated PCa cells (Pesta et al, 2010) and other cancers (Zhang et al, 2018). Ambs et al, (2008) suggested that microRNA expression changes with development and progression of prostate cancer and microRNAs regulated some of the cancer-related genes.…”
Section: Circulating Mir-20a and Mir-26a As Biomarkers In Prostate Camentioning
confidence: 93%
See 1 more Smart Citation
“…Porkka et al, (2007) identified 51 individual miRNAs which differentially expressed between benign and malignant tumors, among which, 37 showed down-regulation and 14 showed up-regulation in carcinoma samples. In other studies higher levels of miR-20a expression were shown in more dedifferentiated PCa cells (Pesta et al, 2010) and other cancers (Zhang et al, 2018). Ambs et al, (2008) suggested that microRNA expression changes with development and progression of prostate cancer and microRNAs regulated some of the cancer-related genes.…”
Section: Circulating Mir-20a and Mir-26a As Biomarkers In Prostate Camentioning
confidence: 93%
“…We selected miR-20a and miR-26a for analysis based on previous impellent studies which described the importance of these miRNAs in cancers (ParvizHamidi et al, 2018;Xu et al, 2018). For example there are studies expressed that miR-20a regulates cell growth and plays important roles in prostate and other cancers initiation and progression (O'donnell et al, 2005;Pesta et al, 2010;Liu et al, 2012;Xu et al, 2018;Zhang et al, 2018). Shen et al, (2012) represented significant overexpression of miR-20a in plasma from patients with stage 3 PCa tumors compared to stage 2 or below.…”
Section: Circulating Mir-20a and Mir-26a As Biomarkers In Prostate Camentioning
confidence: 99%
“…Zhang et al performed a systematic review where they evaluated the prognostic implication of miR-20a in PCa [34]. In this article, miR-20a was found to be upregulated in the circulatory system in PCa, and this was correlated with a worse OS [34]. They also found miR-20a upregulated in gastric cancer, glioblastoma, lymphoma and non-small-cell lung cancer (NSCLC), correlating with a worse OS and DFS [34].…”
Section: Discussionmentioning
confidence: 94%
“…Zhang et al performed a systematic review where they evaluated the prognostic implication of miR-20a in PCa [34]. In this article, miR-20a was found to be upregulated in the circulatory system in PCa, and this was correlated with a worse OS [34].…”
Section: Discussionmentioning
confidence: 96%
“…It was convincing that changes in miRNA expression and patient survival was consistent in both the peripheral blood and tissues. However, the results may differ on occasion; for example, when Zhang et al [48] elucidated the prognostic value of miR-20a in human cancers, high expression of both circulating and tumorous miR-20a were associated with an unfavorable outcome only in gastrointestinal cancers. In this meta-analysis, all the included studies were related to tissue miRNAs with reliable results.…”
Section: Discussionmentioning
confidence: 99%